Dietary effect of lemon verbena extract on selected blood parameters and on plasma oxidative profile in Avelignese horses. (16th December 2018) - Palazzo, Marisa; Vizzarri, Francesco; Cinone, Mario; D'Alessandro, Angela Gabriella; Martemucci, Giovanni; Casamassima, Donato
Abstract: The effect of Lippia citriodora extract on selected blood parameters and on plasma oxidative markers in Avelignese horses was evaluated. Twenty‐four horses were divided into three groups, consisting of eight animals each. Results of two experimental groups, 0.5 mg of verbascoside per kg of metabolic body weight (bw 0.75 ) in the low‐dose group (LVB) and 1.0 mg of verbascoside per kg of metabolic body weight (bw 0.75 ) in the high‐dose group (HVB), were compared to the control group (CON). Groups fed L. citriodora extract (HVB and LVB) showed a significant decrease in triglycerides, total cholesterol and LDL cholesterol ( p < .01), bilirubin, and transaminases ( p < .05), and an increase in HDL cholesterol ( p < .01) compared to the CON group. Oxidative status was improved due to significant decrease in plasma concentration of ROMs and TBARS ( p < .01) and increase in levels of vitamin A and vitamin E ( p < .01). Based on obtained results, it is assumed that dietary supplementation with L. citriodora extract might find a useful application in horse feeding, with positive impact observed in blood parameters and plasma oxidative markers, with beneficial effects on the physiological welfare of livestock animals.